Effect of temperature on ammonium removal in Scenedesmus sp. (September 2015) - Ruiz-Martínez, A.; Serralta, J.; Seco, A.; Ferrer, J.
Highlights: Ratkowsky's model accurately reproduced the temperature effect on ammonium removal. Cardinal temperatures model (CTM) obtained analogous results as Ratkowsky's equation. The CTM is preferred due to the biological significance of its parameters. The obtained theoretical optimum temperature for ammonium removal was 31 °C. Abstract: The effect of temperature on microalgal ammonium uptake was investigated by carrying out four batch experiments in which a mixed culture of microalgae, composed mainly of Scenedesmus sp., was cultivated under different temperatures within the usual temperature working range in Mediterranean climate (15–34 °C). Ammonium removal rates increased with temperature up to 26 °C and stabilized thereafter. Ratkowsky and Cardinal temperatures models successfully reproduced the experimental data. Optimum (31.3 °C), minimum (8.8 °C) and maximum (46.1 °C) temperatures for ammonium removal by Scenedesmus sp. under the studied conditions were obtained as model parameters. These temperature-related parameters constitute very useful information for designing and operating wastewater treatment systems using these microalgae.